If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 1) = 1 + -1x Reorder the terms: 2(1 + 3x) = 1 + -1x (1 * 2 + 3x * 2) = 1 + -1x (2 + 6x) = 1 + -1x Solving 2 + 6x = 1 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 2 + 6x + x = 1 + -1x + x Combine like terms: 6x + x = 7x 2 + 7x = 1 + -1x + x Combine like terms: -1x + x = 0 2 + 7x = 1 + 0 2 + 7x = 1 Add '-2' to each side of the equation. 2 + -2 + 7x = 1 + -2 Combine like terms: 2 + -2 = 0 0 + 7x = 1 + -2 7x = 1 + -2 Combine like terms: 1 + -2 = -1 7x = -1 Divide each side by '7'. x = -0.1428571429 Simplifying x = -0.1428571429
| 1=2x-6 | | 2(5x+35)=40 | | B^4+5b^2-24= | | 5y=-0+20 | | B^2+5x+6= | | 5x+15=90 | | 6x^2+x+1=0 | | 2(4x-3)-7=-45 | | 5x-15=35 | | 3(3x+1)=-42 | | 5(x-5)=-2x+38 | | 48=2(4x+4) | | 2.3=7.9-0.8x | | 4(2a-3)=3(5a-2) | | 5=5(2x+3) | | 6x+21=-33 | | 3x-10=2(3x-2) | | Y^2(y+4)+6(y+4)= | | 4(8x-16)-3(3x-39)=5(5x-40) | | -x+9=x-1 | | -2x+5=-3x+7 | | 2(x-5)+2=-16 | | w-7=-2 | | -3x+19=-6x+46 | | -300+4X=-8X | | 5(x-5)=-30 | | 2(4x-3)=-3x-17 | | 6n-n= | | 2(x+3)+7=-x+46 | | 7x+4=5x+26 | | 3(4x-4)=2x+38 | | 8x+4=5x+1 |